2017
DOI: 10.1186/s13013-017-0113-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic indices for lumbar developmental spinal stenosis

Abstract: BackgroundPatients with developmental spinal stenosis (DSS) are susceptible to developing symptomatic stenosis due to pre-existing narrowed spinal canals. DSS has been previously defined by MRI via the axial anteroposterior (AP) bony spinal canal diameter. However, MRI is hardly a cost-efficient tool for screening patients. X-rays are superior due to its availability and cost, but currently, there is no definition of DSS based on plain radiographs. Thus, the aim of this study is to develop radiographic indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…In the present study, 48 patients in the case group and 13 patients in the control group had anterior-posterior diameter at the intervertebral disc level less than 10mm, which was similar to that of Pawer et al and Cheung et al studies (18)(19). In the study by Cheung et al the mean interpanedular distance was 30 mm at T1 and was 29.8 at T2, which was slightly more than the current study`s result (19). Moreover, in the study by Pawer et al, this distance mean between the patient and healthy group was 30mm (18), which was higher than the mean of current study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, 48 patients in the case group and 13 patients in the control group had anterior-posterior diameter at the intervertebral disc level less than 10mm, which was similar to that of Pawer et al and Cheung et al studies (18)(19). In the study by Cheung et al the mean interpanedular distance was 30 mm at T1 and was 29.8 at T2, which was slightly more than the current study`s result (19). Moreover, in the study by Pawer et al, this distance mean between the patient and healthy group was 30mm (18), which was higher than the mean of current study.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that the posterior-anterior diameter of the bony canal has little diagnostic importance and that what is important in this parameter, is the examination of the same area in the myelogram to examine the dural sac (7). In the present study, 48 patients in the case group and 13 patients in the control group had anterior-posterior diameter at the intervertebral disc level less than 10mm, which was similar to that of Pawer et al and Cheung et al studies (18)(19). In the study by Cheung et al the mean interpanedular distance was 30 mm at T1 and was 29.8 at T2, which was slightly more than the current study`s result (19).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is an important factor to consider in spinal stenosis surgery as patients with DSS have a high reoperation rate of up to 22% [23][24][25] . A large amount of studies focused on defining DSS radiologically 22,[26][27][28][29][30][31] , but only a few investigated its clinical course and clinical presentation 9,32 . Subjects with DSS are found to have earlier onset of symptoms during their fourth or fifth decades 33 as mild degenerative changes of the lumbar spine are already sufficient to compress the neural elements.…”
Section: Introductionmentioning
confidence: 99%
“…One must appreciate the unique pathological characteristics of DSS that distinguish it from degenerative/acquired lumbar spinal stenosis. Previous studies have characterized DSS with both x‐ray and magnetic resonance imaging (MRI) phenotyping, having a paradoxical relationship with ligamentum flavum hypertrophy, and possible genetic origins . Yet, further understanding of its pathophysiology is necessary to determine the clinical significance of DSS.…”
mentioning
confidence: 99%